The last Ottoman wars : the human cost, 1877-1923 - Salt, Jeremy (The University of Utah Press, 2019)
"Jeremy Salt's manuscript "The last Ottoman wars" is a unique, timely, and humane study of warfare and its many costs in a region that has been fought over and upon for centuries. The Ottoman Empire and its surrounding territories, which in this work covers the Balkans to eastern Anatolia and the Caucasus, was during the last decades of the nineteenth century and the first decades of the twentieth a place of political unrest and constant military action. Historians have since chronicled and contested questions of how, what, where, when, and why battlefield or diplomatic strategies failed or succeeded as they did in Ottoman-European conflicts. So too have historians questioned how and to what degree the actions of generals and statesmen, as well as financiers, resulted in ruin for millions of Ottoman peoples, specifically Armenians and other Ottoman Christians. Overlooked, according to Salt, have been millions of Ottoman Muslims, who during the time period in question were massacred and displaced before the advance and against the retreat of invading armies. This manuscript is, as Salt writes, an attempt "to bring these invisible victims of war back into the picture." "The Last Ottoman Wars" offers readers a glimpse into the daily lives of Ottoman Muslims, and indeed all ordinary Ottoman citizens. Instead of following the nations and individuals desperate to get what spoils they could from an empire in decline, Salt centers his focus on those left to live with what remained after nearly all had been taken. These people, at the edge of modernity, lived with malnutrition, disease, internecine violence, and crumbling infrastructures a generation before World War I and immediately after its devastation"--Provided by publisher.